Overcoming Arabic Learning Barriers in MI Muhammadiyah Tambaksari Blora: SDGs-Oriented Approaches - Widodo; Armin Nurhartanto; Alberto Emmanuel Conti Morales (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to identify barriers in Arabic language learning at MI Muhammadiyah Tambaksari, Blora and to propose practical solutions to improve learning effectiveness in a rural madrasah context. Theoretical framework: The study is grounded in SDG 4 (Quality Education) within the United Nations Sustainable Development Goals, emphasising inclusive, equitable, and sustainable primary education as an analytical lens. Literature review: Previous studies report challenges in Arabic learning related to media, motivation, methods, and teacher competence, but rarely connect these issues to sustainability and global education frameworks. Methods: This research uses a qualitative descriptive case study approach, with data collected through observations, interviews, and document analysis, and analysed using descriptive qualitative techniques. Results: The findings reveal several key barriers to Arabic language learning at MI Muhammadiyah Tambaksari Blora, including limited learning media, low student motivation, insufficient lesson hours, mismatched teacher educational backgrounds, and the lack of a supportive Arabic language environment. These factors are interrelated and collectively reduce the effectiveness of Arabic language instruction, particularly in developing balanced language skills. Implications: The study recommends SDGs-oriented strategies such as interactive media development, varied teaching methods, teacher competency improvement, time optimisation, and supportive language environments to enhance learning quality. Novelty: This study is novel in applying SDG 4 to link local Arabic learning problems with sustainable and inclusive education, offering a context-sensitive model for rural Islamic primary schools.